KAJIAN PEMANENAN AIR HUJAN SEBAGAI ALTERNATIF SUMBER AIR BERSIH DI PERKOTAAN - Singal, Rachel Zandra; Sakkia, Nur (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
ABSTRACT: Rainwater Harvesting (RWH) is a method used to collect and store rainwater from rooftops, buildings, or the ground during rainy seasons, as a source of clean water. Rainwater utilization can be used to address clean water scarcity, reduce runoff volume, and replenish groundwater, especially in urban areas. Tanjung Selor, the capital of North Kalimantan Province, is experiencing rapid development, particularly in housing development, due to its rapid population growth. Conditions in urban areas, particularly Tanjung Selor, have resulted in high demand for clean water, which can lead to water shortages in residential areas and surrounding areas. Rainwater harvesting is an alternative to reduce clean water shortages. Rainwater harvesting can meet water needs while simultaneously saving on the use of PDAM (State Water Company) and groundwater. Rainwater that can be collected by the Rainwater Harvesting system in the Global KM 6 Housing with a roof area of 36 m2 type houses each month is a minimum of 2.37 m3 and a maximum of 31,26 m3. The needs of each housing unit with an estimated number of occupants of 3 people are 10,8 m3 each month. So the volume of rainwater harvested from the PAH system for minimum conditions compared to the water needs of each housing unit is still insufficient to meet the need for clean water. And the volume of rainwater harvested from the PAH system for maximum conditions compared to the water needs of each housing unit is sufficient to meet the need for clean water in the housing. If the RWH conditions are minimal, it is recommended that additional clean water from other sources, namely PDAM for housing.Keywords: Rainfall, Clean Water, Groundwater, Building Roofs, Tanjung SelorABSTRAK: Pemanenan Air Hujan (PAH) merupakan cara yang digunakan untuk mengumpulkan dan menyimpan air hujan dari atap rumah, atap gedung atau di permukaan tanah pada saat hujan, sebagai salah satu sumber air bersih. Pemanfaatan air hujan dapat digunakan untuk mengatasi permasalahan kelangkaan air bersih, mengurangi volume air limpasan hujan dan mengisi kembali air tanah terutama di perkotaan. Tanjung Selor merupakan Ibu Kota Provinsi Kalimantan Utara yang sedang berkembang terutama pembangunan perumahan karena pesatnya pertumbuhan penduduk. Kondisi di perkotaan khususnya kota Tanjung Selor ini memicu konsekuensi bahwa kebutuhan air bersih yang tinggi dapat memicu pula kelangkaan air bersih di wilayah perumahan dan sekitarnya. Pemanenan Air Hujan merupakan salah satu alternatif untuk mengurangi terjadinya kekurangan air bersih. Sehingga panen air hujan dapat memenuhi kebutuhan air sekaligus dapat menghemat pengunaan PDAM ataupun air tanah. Air hujan yang dapat ditampung dengan sistem Pemanenan Air Hujan di Perumahan Global KM 6 dengan luas atap rumah type 36 M2 tiap bulannya minimal adalah 2,37 m3 dan maksimal 31,26 m3. Kebutuhan tiap unit rumah dengan estimasi jumlah penghuni 3 orang yaitu 10,8 m3 tiap bulan. Sehingga jumlah volume air hujan yang di panen dari sistem PAH untuk kondisi minimal dibandingkan kebutuhan air pada tiap unit rumah masih kurang untuk memenuhi kebutuhan air bersih. Dan jumlah volume air hujan yang di panen dari sistem PAH untuk kondisi maksimal dibandingkan kebutuhan air pada tiap unit rumah cukup untuk memenuhi kebutuhan air bersih di perumahan. Jika kondisi PAH minimal disarankan perlu penambahan air bersih dari sumber lain yaitu PDAM untuk perumahan.Kata kunci: Curah Hujan, Air Bersih, Air Tanah, Atap Bangunan, Tanjung Selor